2009
DOI: 10.1007/s11104-009-0235-3
|View full text |Cite
|
Sign up to set email alerts
|

Copper uptake kinetics in hydroponically-grown durum wheat (Triticum turgidum durum L.) as compared with soil’s ability to supply copper

Abstract: This study investigated (a) net Cu uptake kinetics in durum wheat (Triticum turgidum durum L.) exposed to free Cu 2+ activities in solution ranging from 0.4 to 2,420 nM and (b) the relative importance of plant uptake and soil's ability to supply Cu 2+ to the roots. Plant Cu flux showed a hyperbolic shape, enabling to estimate the Michaelis-Menten kinetic parameters (F max and K M ) for durum wheat. Plant Cu flux was then compared with soil Cu flux as assessed by the Diffusive Gradient in Thin film technique on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 49 publications
3
15
0
1
Order By: Relevance
“…During the growth cycle, the higher level of Cu in the roots of both treatments (Table 2) resulted in the strong capacity of these tissues to hold Cu against its transport to the leaves (Loneragan 1981;Kabata-Pendias and Pendias 1992), as previously also found in this genotype (Lidon and Henriques 1993a). Indeed, in Oryza sativa L. cv Safari, Cu uptake is an active process (Lidon and Henriques 1993a;Bravin et al 2009), this metal being almost entirely retained in complexed forms (Lidon and Henriques 1994;Bravin et al 2009), namely in cell walls Henriques 1994, 1998). Nevertheless, probably because of the higher electrolytic conductance, the higher content of this metal in the roots of UV-B-stressed rice (Table 2) also indicated an increasing passive uptake that promoted a slight increase in this metal's concentration in the leaves.…”
Section: Discussionsupporting
confidence: 58%
“…During the growth cycle, the higher level of Cu in the roots of both treatments (Table 2) resulted in the strong capacity of these tissues to hold Cu against its transport to the leaves (Loneragan 1981;Kabata-Pendias and Pendias 1992), as previously also found in this genotype (Lidon and Henriques 1993a). Indeed, in Oryza sativa L. cv Safari, Cu uptake is an active process (Lidon and Henriques 1993a;Bravin et al 2009), this metal being almost entirely retained in complexed forms (Lidon and Henriques 1994;Bravin et al 2009), namely in cell walls Henriques 1994, 1998). Nevertheless, probably because of the higher electrolytic conductance, the higher content of this metal in the roots of UV-B-stressed rice (Table 2) also indicated an increasing passive uptake that promoted a slight increase in this metal's concentration in the leaves.…”
Section: Discussionsupporting
confidence: 58%
“…Analogous to the above research, a hydroponic study was carried out on durum wheat grown under variable Cu stress levels exposed for 8 days, and results showed that 2420 nM Cu decreased root length and inhibited the lateral root formation ( Fig. 3; Bravin et al 2010). In the same manner, excess of Cu in the culture medium results in stunted root growth of durum wheat, and roots appeared thick and brown at higher concentrations (Michaud et al 2008;Rizwan 2012).…”
Section: Effect On Plant Growth and Morphologymentioning
confidence: 78%
“…In durum wheat, excess Cu during vegetative stage resulted to chlorosis on leaves ( Fig. 3; Michaud et al 2007Michaud et al , 2008Bravin et al 2009Bravin et al , 2010Rizwan 2012).…”
Section: Effect On Plant Growth and Morphologymentioning
confidence: 99%
“…through oxidative damages or by interaction with proteins) or indirectly through disrupting absorption, transport, and functioning of other nutrient elements (Yruela 2009). In comparing tissue Cu content in our experiments with that of Bravin et al (2010) for durum wheat, one may assume that the shoot content at 600Cu (18 mg kg (1 ) was not toxic; however, at 400Cu the root content (187 mg kg…”
Section: Separate Effect Of Excess Coppermentioning
confidence: 93%